The Relationship Between Mindset and Poverty Levels in Kisinga Sub-County Kasese District - Kambere, Roggers (Kabale University, 2024)
The study explored the causes of poverty in rural areas of Kasese district. The study was guided by objectives like identifying the government policies on poverty reduction in the Kasese district, examining the effects of poverty in rural areas in the Kasese district, and identifying the challenges hindering poverty reduction strategies in rural areas in the Kasese district. The study sampled a total of 131 who were collected and used in the analysis. Data was collected through questionnaires and interviews. The research used a cross-sectional study design. Research findings showed that levels of stress in the family have also been shown to correlate with economic circumstances due to high levels of poverty in rural areas. Children raised in poverty tend to miss school more often because of illness whereby in the family there is no money to take such a child to the hospital and also to school and this has increased the levels of learners' dropout. There is a challenge of farming systems whereby farmers since the majority of respondents spend much of their attention on food production just for home consumption and therefore they produce less for the markets that can help them generate some money that can help to meet the basic needs, poor finance policies in rural areas. European Union policies on agriculture should be followed since agricultural policy plays an important role in supporting the income of small and medium-size enterprises that are very important in the EU agricultural production. Banks should improve their services to small-scale farmers and enterprises by syndicating small loans with financial cooperatives and community banks, thereby promoting resource mobilization and financial intermediation in rural areas. The study concludes that most of the residents were involved in rural development in rural areas. Both household asset endowments (in particular, land, livestock, and education) and incentives in the economic system (road network and infrastructure, information and market access, availability of public goods and services, agro-ecological conditions, etc.) constrain households from participating in high return livelihood strategies. The study recommends that rural infrastructure and education should receive higher priority in the public investment portfolio. Investments in infrastructure and education reduce rural poverty mainly by spurring nonfarm employment and growth in agricultural productivity. Uganda should continue its investments in health care, but future investments should be geared toward improving the efficiency of existing public health-care systems. The government should drastically increase its investment in this region, governance and security concerns permitting.